(untitled) (Comillas Journal of International Relations, 2020)
The aim of this article is to analyze the process of experiential education developed with the implementation of the models of negotiation in real scenarios at the Universidad Pontificia Bolivariana (Colombia) and determine the main aspects that could be considered by the delegations participating in the selection process, the preparation, the development and the simulation in this type of models. To achieve this objective, the methodology that was developed was based on the analysis of 102 surveys to delegates from 42 universities in 12 countries that have already participated in the negotiating models in the period of 2014-2018. The results suggest that the respondents consider that the main benefit from their participation in the models is the experience gained in the knowledge of the management of global affairs; at the same time, respondents consider that they gain skills by working under pressure; in the same way, they believe that the knowledge acquired as a result of their participation in these models is related to topics about cross-cultural negotiation. Finally, it is determined that the main adversity that the delegates have faced during the models, is the interaction with other participants due to the ideological differences, cultural and idiomatic expressions.